2003
DOI: 10.1038/sj.onc.1206583
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of NF-κB by genistein is mediated via Akt signaling pathway in breast cancer cells

Abstract: Genistein, a natural isoflavonoid found in soybean products, has been proposed to be associated with a lower rate of breast cancer in Asian women. Studies from our laboratory and others have shown that genistein can induce apoptosis by regulating the expression of apoptosis-related genes in breast cancer cells. However, the precise molecular mechanism(s) by which genistein induces apoptotic cell death is not clear. In order to investigate such mechanism, we tested the role of Akt and NF-jB in genistein-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
139
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 45 publications
16
139
0
4
Order By: Relevance
“…[5][6][7][8][9][10] Our previous studies also showed that genistein can induce apoptosis and inhibit NF-jB activation in pancreatic cancer cells. 8,9,11 NF-jB plays important roles in the control of cell growth, differentiation, apoptosis and inflammation. 12 NF-jB mediates survival signals that inhibit apoptosis and promote cancer cell growth.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Our previous studies also showed that genistein can induce apoptosis and inhibit NF-jB activation in pancreatic cancer cells. 8,9,11 NF-jB plays important roles in the control of cell growth, differentiation, apoptosis and inflammation. 12 NF-jB mediates survival signals that inhibit apoptosis and promote cancer cell growth.…”
mentioning
confidence: 99%
“…Polyphenolic compounds from various herbs have been found to work as phytoestrogens (Mitchell et al, 2000;Gong et al, 2003;Klinge et al, 2005), antioxidants (Rüfer and Kulling, 2006), tyrosine kinase inhibitors (Kousidou et al, 2006), and anti-inflammatory compounds (Jung et al, 2007). HPLC analysis of AR displayed the presence of several secondary metabolites such as polyphenolic flavonoids including formononetin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, genistein inhibited cell growth and induced apoptosis of breast cancer cells through the down-regulation of AKT, ERK, NF-jB and AP-1 [131], which suggested that the inactivation of NF-jB is partly mediated by AKT and demonstrated the crosstalk between AKT and NF-jB pathways [131].…”
Section: Inhibition Of Signalling Through Nf-jbmentioning
confidence: 99%